Non-linear growth analysis of Sumatera thin tail sheep and its cross breds - Suparyanto, Agus; ., Subandriyo; Widarya, T.R; Martojo, H.H (Indonesian Journal of Animal and Veterinary Sciences, 2001)
Growth curve is a figure of individual ability to express its genetic potential to maximum size under the existingenvironmental condition. Three non-linear growth curves, von Bertalanffy, Logistic and Gompertz, were used to analyze the weight-age relationship for five genotypes of sheep. The data were collected from IP2TP Sei Putih, North Sumatera. Num ber of animals which were collected consisted of five genotypes i.e, indigenous Sumatera (n=275), St. Croix (n=571), St. Croix Cross (n=899), Barbados Blackbelly Cross (n=471) and composite (n=740). The three non-linear growth curves were compared to obtain the most suitable curve for describing the shape of growth curves among sheep genotypes. The growth curves of von Bertalanffy fitted better than the others. The results showed that regression parameters of B or M (integral constante) were significantly different (P<0.001) among growth curves. It means that higher asymptotic weights will be followed by faster growth rates to reach mature size. Value of A (asymptotic mature weigh) and k (growth rate to mature size) were not significant (P>0.05). The data show that there was correlation between A and k. Â  Key words: Sumatera thin-tail sheep, crossing, non-linear growth